Ordered‐Mesoporous‐Carbon‐Confined Pb/PbO Composites: Superior Electrocatalysts for CO2 Reduction. Issue 23 (20th April 2020) - Huang, Xin; Song, Jinliang; Wu, Haoran; Xie, Chao; Hua, Manli; Hu, Yue; Han, Buxing
Abstract: CO2 electroreduction has gained significant interest. However, fabricating cost‐effective nonprecious‐metal electrocatalysts that can selectively convert CO2 to a specific product remains highly challenging. Herein, Pb‐based materials consisting of Pb 0 and PbO confined in ordered mesoporous carbon (OMC) (Pb/PbO@OMC) were constructed for CO2 electroreduction to CO. Interestingly, the activity and selectivity of the Pb/PbO@OMC varied with the molar ratio of Pb 0 /PbO. The material calcined at 800 °C (Pb/PbO@OMC‐800) with a Pb 0 /PbO ratio of 0.58 provided the best result with CO as the only carbon‐based product, and the Faradaic efficiency of CO reached 98.3 % at a high current density of 41.3 mA cm −2 . Detailed studies indicated that Pb 0, PbO, and OMC co‐operated well to enhance the performance of Pb/PbO@OMC‐800, which mainly originated from the good interface between Pb 0 and PbO, higher electrochemical active surface area, and faster electron transfer to form the CO2 ⋅− intermediate. Abstract : The CO‐op ! Ordered mesoporous carbon (OMC)‐confined Pb‐based materials were constructed for CO2 electroreduction to CO. The material calcined at 800 °C (Pb/PbO@OMC‐800) provided the best result with CO as the only carbon‐based product, and the Faradaic efficiency of CO reached 98.3 % at a high current density of 41.3 mA cm −2 . Detailed studies indicated that Pb 0, PbO, and OMC co‐operated well to enhance the performance of Pb/PbO@OMC‐800.